Electrolytic copper foil for secondary batteries and its manufacturing method

JP7643655B2Active Publication Date: 2025-03-11LOTTE ENERGY MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021163962
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-11-11
Filing Date
2021-10-05
Publication Date
2025-03-11
Estimated Expiration
2037-03-28

AI Technical Summary

Benefits of technology

【0023】 本発明によれば、銅電解液にTOC及び金属添加剤であるコバルト及び鉄を一定の含有量で存在するようにして、銅箔のめっき時の結晶構造の変形を防いで、電池の充放電特性が優れて現れる二次電池用電解銅箔を製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643655000006
    Figure 0007643655000006
  • Figure 0007643655000007
    Figure 0007643655000007
  • Figure 0007643655000001
    Figure 0007643655000001
Patent Text Reader

Abstract

Provided is an electrolytic copper foil for secondary batteries which exhibits little change in physical properties due to differences in crosshead speed when measuring the tensile strength and elongation of the electrolytic copper foil, has excellent battery charge / discharge characteristics, and can prevent detachment of active material. [Solution] An embodiment of the present invention is an electrolytic copper foil for a secondary battery, which is manufactured using a drum with a plating solution containing TOC, cobalt, and iron, and is coated with a negative electrode active material, and the ratio of TOC, cobalt, and iron contained in the electrolytic copper foil satisfies the following formula 1: Equation 1: TOC / (cobalt + iron) = 1.3-1.5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an electrodeposited copper foil for a secondary battery and a manufacturing method thereof, and more particularly to an electrodeposited copper foil for a secondary battery which exhibits small changes in physical properties due to differences in crosshead speed when measuring the tensile strength and elongation of the electrodeposited copper foil, has excellent battery charge / discharge characteristics, and is capable of preventing detachment of an active material, and a manufacturing method thereof. [Background technology]

[0002] Generally, electrolytic copper foil is widely used as a basic material for PCBs (Printed Circuit Boards) in the electrical / electronics industry, and demand for it is rapidly increasing, especially for small products such as slim notebook computers, personal digital assistants (PDAs), e-books, MP3 players, next-generation mobile phones, and ultra-thin flat panel displays. Furthermore, by improving the physical properties of electrolytic copper foil, it is also widely used as a cathode current collector for secondary batteries.

[0003] Typically, electrolytic copper foil is produced by electrolysis in an electrolytic cell containing a cylindrical titanium cathode (also called a drum), a lead alloy or iridium oxide-coated titanium anode spaced apart, an electrolyte, and a power source. The electrolyte consists of sulfuric acid and / or copper sulfate. When a direct current is applied between the cathode and anode while the cylindrical cathode is rotating, copper is electrodeposited onto the cathode, enabling continuous production of electrolytic copper foil. This process of reducing copper ions to metal by electrolysis is called the foil-making process.

[0004] The copper foil obtained in the foil manufacturing process can then undergo additional surface treatment processes, such as a nodule treatment process to improve adhesion to the insulating substrate, a diffusion prevention process to prevent the diffusion of copper ions, a rust prevention process to prevent external oxidation, and a chemical adhesion improvement process to complement adhesion to the insulating substrate, if necessary. After undergoing these surface treatment processes, the foil becomes copper foil for low-profile printed circuits, and if only rust prevention treatment is performed among the surface treatment processes, it becomes copper foil for secondary batteries.

[0005] When electrodeposited copper foil is used for printed circuits, it is supplied to PCB processors in a laminated form with an insulating substrate after undergoing surface treatment, whereas when it is used for secondary batteries, it is supplied to secondary battery manufacturers only after undergoing anti-rust treatment.

[0006] When an electrolytic copper foil is used as a cathode current collector for a secondary battery, both sides of the copper foil are coated with an electrode active material. In this case, if the roughness of both sides of the electrolytic copper foil differs, the battery characteristics will differ, so it is necessary to maintain the roughness of both sides of the electrolytic copper foil at the same level.

[0007] Meanwhile, when testing the tensile strength and elongation of copper foil, if there is a large difference due to the crosshead speed, the physical properties of the copper foil change, deteriorating the charge / discharge characteristics of the battery and causing phenomena such as cracking or active material detachment. This phenomenon occurs when the crystalline structure of the copper foil is deformed during electrolytic plating, and if cracks occur in the battery or active material detachment occurs, there is a problem of shortening the battery life.

[0008] Therefore, there is a demand for an electrodeposited copper foil for secondary batteries that can prevent the crystal structure of the copper foil from being deformed during electrolytic plating, minimizes the difference due to the crosshead speed during physical property testing of the copper foil, and has excellent battery charge / discharge characteristics. Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention relates to an electrodeposited copper foil for secondary batteries, which exhibits excellent charge-discharge characteristics by preventing deformation of the crystalline structure during plating of copper foil by making TOC and metal additives, cobalt and iron, present in a copper electrolyte at a certain content, and a method for producing the same.

[0010] The present invention also relates to an electrodeposited copper foil for a secondary battery, which exhibits little change in properties even when the crosshead speed is changed when measuring the cathode properties of the electrodeposited copper foil, and which can prevent cracks or detachment of active material from occurring in the battery, and a method for manufacturing the same. [Means for solving the problem]

[0011] According to one aspect of the present invention, an embodiment of the present invention provides an electrodeposited copper foil for a secondary battery, which is manufactured using a drum with a plating solution containing TOC (total organic carbon), cobalt, and iron, and is coated with a cathode active material, wherein the ratio of TOC, cobalt, and iron contained in the electrodeposited copper foil satisfies the following formula 1:

[0012] Equation 1: TOC / (cobalt + iron) = 1.3-1.5 The electrodeposited copper foil is characterized in that the crosshead speed difference for measuring the tensile strength at room temperature and at 110°C (6 hours) satisfies Equation 2, and the crosshead speed difference for measuring the elongation at room temperature and at 110°C (6 hours) satisfies Equation 3.

[0013] Formula 2: (1mm / min crosshead speed tensile strength) / (50mm / min crosshead speed tensile strength)≧0.9 Formula 3: (1 mm / min crosshead speed elongation rate) / (50 mm / min crosshead speed elongation rate)≧0.8 The plating solution is characterized in that the concentration of TOC contained therein is 100 ppm or more.

[0014] The room temperature tensile strength of the electrolytic copper foil is 40 kgf / mm 2~51kgf / mm 2 It is characterized in that:

[0015] The thickness of the electrolytic copper foil is 4 μm to 12 μm.

[0016] The electrolytic copper foil has a stretch ratio of 2% to 18%.

[0017] According to one aspect of the present invention, an embodiment of the present invention is a method for manufacturing an electrodeposited copper foil for a secondary battery, comprising: (1) preparing a plating solution containing copper, TOC, cobalt, and iron; (2) performing electroplating using a drum at a temperature of 30°C to 70°C and a current density of 30 ASD to 150 ASD; and (3) coating a cathode active material on the electrodeposited copper foil formed by the electroplating, wherein the ratio of TOC, cobalt, and iron contained in the electrodeposited copper foil satisfies the following formula 1: include.

[0018] Equation 1: TOC / (cobalt + iron) = 1.3-1.5 The electrodeposited copper foil is characterized in that the crosshead speed difference for measuring the tensile strength at room temperature and at 110°C (6 hours) satisfies Equation 2, and the crosshead speed difference for measuring the elongation at room temperature and at 110°C (6 hours) satisfies Equation 3.

[0019] Formula 2: (1mm / min crosshead speed tensile strength) / (50mm / min crosshead speed tensile strength)≧0.9 Formula 3: (1 mm / min crosshead speed elongation rate) / (50 mm / min crosshead speed elongation rate)≧0.8 The plating solution is characterized in that the concentration of TOC contained therein is 100 ppm or more.

[0020] The room temperature tensile strength of the electrolytic copper foil is 40 kgf / mm 2 ~51kgf / mm 2It is characterized in that:

[0021] The thickness of the electrolytic copper foil is 4 μm to 12 μm.

[0022] The electrolytic copper foil has a stretch ratio of 2% to 18%. [Effects of the Invention]

[0023] According to the present invention, by making TOC and metal additives, cobalt and iron, present in a certain content in the copper electrolyte, deformation of the crystalline structure during plating of the copper foil can be prevented, and an electrodeposited copper foil for a secondary battery exhibiting excellent charge / discharge characteristics of the battery can be produced.

[0024] Furthermore, according to the present invention, an electrolytic copper foil is produced which exhibits little change in properties due to a change in crosshead speed when measuring the cathode properties of the electrolytic copper foil, thereby preventing cracks or detachment of the active material in the battery. [Brief explanation of the drawings]

[0025] [Figure 1] 1 is a flowchart showing a method for manufacturing an electrolytic copper foil for a secondary battery according to an embodiment of the present invention. [Figure 2] 1 is a diagram illustrating a process for manufacturing an electrolytic copper foil using a drum according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0026] Further details of the embodiments are included in the detailed description and drawings.

[0027] The advantages and features of the present invention, and methods for achieving them, will become clearer with reference to the following detailed description of the embodiments in conjunction with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below, and may be embodied in various different forms. In the following description, when a part is referred to as being connected to another part, this includes not only a direct connection but also a connection via an intermediate medium. In addition, parts not related to the present invention are omitted in the drawings to clarify the description of the present invention, and similar parts are designated by the same reference numerals throughout the specification.

[0028] The present invention will now be described with reference to the accompanying drawings.

[0029] Next, the electrolytic copper foil for a secondary battery according to an embodiment of the present invention will be described in more detail.

[0030] An electrolytic copper foil for a secondary battery according to one embodiment of the present invention is an electrolytic copper foil for a secondary battery manufactured using a drum and coated with a negative electrode active material, the electrolytic copper foil comprising an electrolytic copper foil for a secondary battery, the crosshead speed difference for measuring tensile strength at room temperature and at 110°C (6 hours) being in accordance with Equation 2, and the crosshead speed difference for measuring elongation at room temperature and at 110°C (6 hours) being in accordance with Equation 3.

[0031] Formula 2: (1mm / min crosshead speed tensile strength) / (50mm / min crosshead speed tensile strength)≧0.9 Formula 3: (1 mm / min crosshead speed elongation rate) / (50 mm / min crosshead speed elongation rate)≧0.8 Increasing the crosshead speed during tensile testing of electrolytic copper foil improves the battery's charge / discharge characteristics and prevents cracks and active material detachment by keeping the physical properties of the copper foil constant even when various peak loads are applied. However, increasing the crosshead speed during tensile testing of copper foil increases the peak load, and when the peak load increases, the tensile strength is measured as high and the elongation rate is reduced. In addition, in the case of thin electrolytic copper foil, the notch effect is small, so the elongation rate is measured as relatively high.

[0032] *On the other hand, when the crosshead speed is low, the peak load is low and the tensile strength is measured low, and in these cases the notch effect is significant, and in the case of general electrolytic copper foil, the tensile strength and elongation rate are reduced. Therefore, since there is little difference due to the measurement speed when measuring the cathode properties of the substrate, after increasing the loading amount of active material when manufacturing the cathode on the substrate, it is possible to prevent cracks in the substrate and detachment of the active material during charge and discharge.

[0033] In the present invention, the change in physical properties due to the difference in crosshead speed for measuring tensile strength and elongation not only at room temperature but also at a high temperature of 110°C follows Equations 2 and 3. This is because, in order to minimize the difference due to the measurement speed of the crosshead speed in the present invention, the TOC content in the copper electrolyte is set to 100 ppm or more, and this can prevent the change in physical properties even when various peak loads are applied depending on the battery design and the loading amount of the active material.

[0034] TOC, an abbreviation for Total Organic Carbon, refers to the total organic carbon and refers to the amount of carbon in organic matter contained in the plating solution. It is included in copper electrolytes to minimize variations in crosshead speed during tensile testing of copper foil. If the copper electrolyte contains dissolve carbon dioxide (TIC) or carbon adsorbed to copper ions, additives present within the grains can diffuse to grain boundaries during prolonged exposure to high temperatures, causing abnormal grain growth and changes in the crystalline structure. However, when TOC is present in copper electrolytes at 100 ppm or more, as in the present invention, it prevents deformation of the crystalline structure during electroplating and maintains consistent physical properties even under various peak loads.

[0035] Therefore, the electrodeposited copper foil for secondary batteries according to the present invention has the advantage that the difference in tensile strength and elongation rate at a crosshead speed is small even at room temperature and at a high temperature (110° C.), and the charge / discharge characteristics of the battery are excellent.

[0036] Therefore, as described above, in the electrodeposited copper foil for a secondary battery according to the present invention, the difference in the tensile strength and elongation due to the measurement speed of the crosshead speed is preferably within the range of the above-mentioned formulas 2 and 3. When the difference in the crosshead speed for measuring the tensile strength at room temperature and at 110°C is less than 0.9, detachment of the active material and cracks may occur, resulting in a shortened battery life. When the difference in the crosshead speed for measuring the elongation at room temperature and at 110°C is less than 0.8, detachment of the active material and cracks may occur, resulting in a shortened battery life.

[0037] FIG. 1 is a flowchart showing a method for manufacturing an electrodeposited copper foil for a secondary battery according to an embodiment of the present invention. Referring to FIG. 1, the method for manufacturing an electrodeposited copper foil for a secondary battery according to the present invention includes the steps of: (1) adding copper ions (Cu 2+(1) preparing a plating solution containing 60 g / L to 140 g / L of ZnO, 70 g / L to 200 g / L of sulfuric acid, 10 ppm to 90 ppm of chlorine, 100 ppm or more of TOC, cobalt, and iron (S100); (2) performing electroplating using a drum at a temperature of 30°C to 70°C and a current density of 30 ASD to 150 ASD (S200); and (3) coating the electrolytic copper foil formed by the electroplating with a cathode active material (S300).

[0038] In step (1) (S100), a plating solution is prepared by adding copper ions (Cu 2+ A plating solution containing 60g / L to 140g / L of Zn, 70g / L to 200g / L of sulfuric acid, 10ppm to 90ppm of chlorine, 100ppm or more of TOC, cobalt, and iron is prepared. In the plating solution, TOC plays a role in minimizing the difference in crosshead speed due to measurement speed during tensile testing of electrodeposited copper foil coated with a cathode active material.

[0039] In addition, in order to minimize changes in the physical properties of the copper foil due to differences in crosshead speed, the present invention further includes cobalt and iron as metal additives other than TOC. The electrolytic copper foil can be manufactured by electrolytic plating using a plating solution, in which TOC can be contained at a certain content, cobalt can be contained at 1 mg / L to 50 mg / L, and iron can be contained at 400 mg / L to 1100 mg / L.

[0040] In the electrolytic copper foil formed by electroplating using a plating solution containing TOC, cobalt, and iron, the TOC content is preferably 100 ppm or more, and the cobalt and iron contents may be provided so as to correspond to the following formula 1:

[0041] When an electrodeposited copper foil is produced by electroplating a plating solution, the concentrations of additives, such as TOC, cobalt, and iron, contained in the plating solution are not always the same as those of the electrodeposited copper foil produced by electroplating, but may be the same or lower.

[0042] The cobalt and iron adjust the copper plating speed during electroplating to flatten the surface and prevent excessive increase in carbon content inside the electrodeposited copper foil. Therefore, when the ratio of cobalt and iron to TOC in the electrodeposited copper foil is within the range of the following formula 1, changes in the physical properties of the copper foil due to differences in crosshead speed are minimized.

[0043] Equation 1: TOC / (cobalt + iron) = 1.3-1.5 If the ratio of TOC to cobalt and iron is less than 1.3, the content of cobalt and iron added to the plating solution increases, which undesirably suppresses the effect of TOC in the plating solution in preventing abnormal grain growth, while if the ratio exceeds 1.5, the excessive TOC content in the electrodeposited copper foil generates stress in the grains, which causes abnormal grain growth in the electrodeposited copper foil after plating, and when the measurement speed for tensile strength and elongation is changed, the change in the physical properties of the electrodeposited copper foil may become severe. Therefore, in order to minimize the change in the physical properties of the electrodeposited copper foil even when the measurement speed for tensile strength and elongation is changed, it is preferable that the ratio of cobalt and iron to TOC be maintained in the range of 1.3 to 1.5 as shown in Equation 1.

[0044] If the copper ions and sulfate ions in the plating solution are out of the above ranges, there is a problem that the copper foil may not be properly deposited or the hardness of the copper foil may be reduced during subsequent electroplating.

[0045] The plating solution contains 10 to 90 ppm of chlorine, which inhibits crystal growth of CuCl precipitates formed at grain boundary interfaces during electroplating when heated to high temperatures, improving thermal stability at high temperatures. If the chlorine concentration is outside the 10 to 90 ppm range, the tensile strength of the electrodeposited copper foil may decrease, and the thermal stability at high temperatures may be reduced.

[0046] In step (2) (S200), electroplating is performed using a drum with the plating solution prepared in step (1) at a temperature of 30°C to 70°C and a current density of 30 ASD (Amperes per Square Decimetre) to 150 ASD. FIG. 2 illustrates the steps for manufacturing an electrodeposited copper foil using a drum according to one embodiment of the present invention. If the plating temperature and current density are outside the above-described ranges, plating may not be performed normally, resulting in an uneven surface of the electrodeposited copper foil or reduced tensile strength and elongation, which may lead to a deterioration in battery performance.

[0047] Step (3) (S300) includes coating the electrodeposited copper foil formed by electroplating with a cathode active material. The electrodeposited copper foil coated with the cathode active material formed in step (3) (S300) may have a crosshead speed difference for measuring tensile strength at room temperature and at 110°C (6 hours) that satisfies Equation 2, and the crosshead speed difference for measuring elongation at room temperature and at 110°C (6 hours) that satisfies Equation 3.

[0048] Formula 2: (1mm / min crosshead speed tensile strength) / (50mm / min crosshead speed tensile strength)≧0.9 Formula 3: (1 mm / min crosshead speed elongation rate) / (50 mm / min crosshead speed elongation rate)≧0.8 The room temperature tensile strength of the electrodeposited copper foil for secondary batteries according to the present invention is 40 kgf / mm 2 ~51kgf / mm 2 It is preferable that the room temperature tensile strength is 40 kgf / mm 2 If the tensile strength is less than 40 kgf / mm, the electrolytic copper foil may break, causing a short circuit between the anode and cathode. When the secondary battery is charged and discharged, the volume of the secondary battery expands or contracts as other active materials such as graphite exchange lithium ions. At this time, stress is generated due to the expansion or contraction because the active material layer is in close contact with the electrolytic copper foil. Therefore, the tensile strength is 40 kgf / mm. 2If the thickness is less than 1 / 2 mm, the electrolytic copper foil cannot withstand the stress and breaks, making it impossible to maintain the battery performance, and the breakage can cause deformation, resulting in a short circuit between the anode and the cathode.

[0049] In addition, the thickness of the electrolytic copper foil is preferably 4 μm to 12 μm. If the thickness of the electrolytic copper foil is less than 4 μm, the electrolytic copper foil may be easily broken due to its thin thickness, and if the thickness of the electrolytic copper foil is more than 12 μm, the volume and weight of the secondary battery to be manufactured increase, which is undesirable.

[0050] The elongation ratio of the electrolytic copper foil is preferably 2% to 18%. A high elongation ratio of the electrolytic copper foil has the advantages of being able to withstand tension during coating of the active material in the electrode manufacturing process, preventing breakage during the process, and being able to prevent breakage due to stress during the electrode winding process. Furthermore, it prevents a decrease in efficiency and breakage during the charge / discharge cycle of the battery, improving battery performance. However, if the elongation ratio exceeds 18%, the secondary battery may be severely deformed during charge / discharge, leading to short-circuiting, while if the elongation ratio is less than 2%, the electrolytic copper foil may be easily broken.

[0051] The tensile strength and elongation ratio are inversely proportional to each other, i.e., as the tensile strength increases, the elongation ratio decreases, and as the tensile strength decreases, the elongation ratio increases. Therefore, in order to produce an electrodeposited copper foil having high tensile strength while preventing breakage, it is important to maintain the tensile strength and elongation ratio within an appropriate range. Therefore, the tensile strength is set to 40 kgf / mm 2 ~51kgf / mm 2 It is preferable to maintain the elongation ratio in the range of 2% to 18% in order to prevent short-circuiting between the anode and cathode when the secondary battery is deformed.

[0052] Examples and comparative examples of the present invention will be described below. However, the following examples are only preferred examples of the present invention, and the scope of the present invention is not limited to the following examples.

[0053] Experiment 1: Battery life test at room temperature based on TOC concentration, tensile strength, and elongation rate Example 1 A plating solution containing 95 g / L of copper ions, 110 g / L of sulfuric acid, 30 ppm of chlorine, 360 ppm of TOC, 0.025 g / L of cobalt, and 0.75 g / L of iron (total of cobalt and iron: 0.775 g / L) was prepared, and electroplating was performed using a drum at 50°C and a current density of 90 ASD. The cathode active material was coated on the electrolytic copper foil formed by the electroplating.

[0054] (Examples 2 to 8) The plating solution was prepared in the same manner as in Example 1, except that the concentrations of TOC, cobalt, and iron contained in the plating solution were as shown in Tables 2 and 3 below.

[0055] (Comparative Examples 1 to 3) In Comparative Examples 1 to 3, electrolytic copper foils were manufactured under the same conditions as in Example 1, except that the concentrations of TOC, cobalt, and iron in the plating solutions were as shown in Tables 2 and 3 below.

[0056] The experimental conditions of Examples 1 to 8 and Comparative Examples 1 to 3 were the same as those described above. The crosshead speed difference for measuring the tensile strength and elongation of each electrodeposited copper foil for secondary batteries prepared by the above methods, the percentages of TOC, cobalt, and iron after melting the copper foil, and the battery life after 300 cycles were measured and are shown in Tables 2 and 3 below.

[0057] The tensile strength and elongation at room temperature were measured by cutting tensile test specimens of 12.7 mm width x 50 mm gauge length from the electrodeposited copper foils obtained in Examples 1 to 8 and Comparative Examples 1 to 3, and then conducting tensile tests at various crosshead speeds according to IPC-TM-6502.4.18B. The maximum load of the tensile strength was measured as the tensile strength, and the elongation at break was measured as the elongation. The tests were conducted at room temperature (20°C) at crosshead speeds of 1 mm / min and 50 mm / min, respectively.

[0058] The percentages of TOC, cobalt, and iron after dissolving the copper foils were analyzed using inductively coupled plasma mass spectrometry (ICP) after dissolving the electrodeposited copper foils obtained in Examples 1 to 8 and Comparative Examples 1 to 3 in 60 ml of hydrochloric acid (35%) and 40 ml of hydrogen peroxide (30%). The percentages of TOC, cobalt, and iron were calculated using Equation 1, and the results are shown in Table 3.

[0059] The battery evaluation conditions were set as follows, and the cell design, anode, cathode, separator, and electrolyte conditions were set as shown in Table 1 below.

[0060] 1) Constant current charging: Current value 1C, charge end voltage 4.2V 2) Rest for 20 minutes 3) Constant current discharge: Current value 1C, Charge cut-off voltage: 2.5V cut-off 4) 1C=487mAh 5) Cycle: 300 cycles, Temperature: 55℃

[0061] [Table 1] JPEG0007643655000002.jpg129134 JPEG0007643655000003.jpg164130 Referring to Tables 2 and 3, it can be seen that Comparative Examples 1 to 3, in which the TOC concentration was less than 100 ppm, all exhibited crosshead speed differences for measuring tensile strength and elongation using Equation 2 of less than 0.9 and less than 0.8, respectively. On the other hand, it can be seen that Examples 1 to 8, in which the TOC concentration was 100 ppm or more, all exhibited crosshead speed differences for measuring tensile strength and elongation using Equation 2 of greater than 0.9 and greater than 0.8, respectively. When TOC is added to the plating solution at 100 ppm or more during the production of electrodeposited copper foil, it is possible to prevent changes in the crystalline structure of the copper foil during electroplating. Therefore, even if the measurement speed is changed during the measurement of tensile strength and elongation, there is little change in the physical properties of the electrodeposited copper foil, resulting in excellent battery life.

[0062] In addition, in Comparative Examples 1 to 3, in which the ratios of TOC / (cobalt + iron) were all less than 1.3, it was found that the changes in the tensile strength and elongation of the electrodeposited copper foils due to the difference in crosshead speed for measuring the tensile strength and elongation were greater than those in Examples 1 to 8, and the battery life was also very short. When the ratio of TOC / (cobalt + iron) was less than 1.3, the contents of cobalt and iron increased, which made it difficult for TOC in the plating solution to prevent abnormal grain growth, and significant changes in the physical properties of the electrodeposited copper foils occurred after measuring the tensile strength and elongation.

[0063] In addition, the batteries according to Examples 1 to 8 and Comparative Examples 1 to 3, whose capacities after 300 cycles were confirmed from Table 3, were disassembled to check the condition of the electrodeposited copper foil (which served as the cathode plate). It was confirmed that the electrodeposited copper foils according to Examples 1 to 8 had no defects in appearance and were the same as the original. On the other hand, it was confirmed that the electrodeposited copper foils according to Comparative Examples 1 to 3 were partially broken or peeled off, that the cathode active material was partially peeled off from the electrodeposited copper foil according to Comparative Examples 1 and 3, and that broken portions were formed on the outer parts of the electrodeposited copper foils according to Comparative Examples 2 and 3.

[0064] Experiment 2: Battery life test at 110℃ based on TOC concentration, tensile strength, and elongation rate In Experiment 2 of the present invention, the TOC concentration and the amount of metal additive were changed in the electrodeposited copper foil for a secondary battery according to an embodiment of the present invention, and the difference in crosshead speed at the tensile strength and elongation ratio was measured, and the corresponding battery life was measured. The experiment was carried out at a high temperature of 110°C.

[0065] In Experiment 2, the battery evaluation conditions, cell design, anode, cathode, separator, and electrolyte conditions were set in the same manner as in Experiment 1 above.

[0066] In Experiment 2, the experimental conditions of Examples 1 to 8 and Comparative Examples 1 to 3 were set to be the same as those of Experiment 1 to prepare electrodeposited copper foils. The tensile strength, elongation and battery life after 300 cycles were measured in the same manner as in Experiment 1, except that the tensile strength and elongation of each electrodeposited copper foil for secondary batteries prepared by the above methods were measured after treatment at a crosshead speed of 110°C for 6 hours. The results are shown in Tables 4 and 5 below.

[0067] [Table 2] Referring to Tables 4 and 5, it can be seen that in Comparative Examples 1 to 3, in which the TOC concentration was less than 100 ppm, the crosshead speed differences for measuring the tensile strength and elongation ratio according to Equation 2 were all less than 0.9 and less than 0.8, respectively, while in Examples 1 to 8, in which the TOC concentration was 100 ppm or more, the crosshead speed differences for measuring the tensile strength and elongation ratio according to Equation 2 were all 0.9 or more and 0.8 or more, respectively. In addition, in Comparative Examples 1 to 3, in which the TOC / (cobalt + iron) ratio was less than 1.3, the changes in the tensile strength and elongation ratio of the electrodeposited copper foils due to the crosshead speed difference for measuring the tensile strength and elongation ratio were greater than those in Examples 1 to 8, and the battery life was also significantly shorter.

[0068] Therefore, it can be seen that the electrodeposited copper foil for secondary batteries according to the present invention has metal additives, cobalt, iron, and TOC, present in a certain content inside the copper foil, thereby minimizing changes in the physical properties of the electrodeposited copper foil even at room temperature and high temperature (110°C). In addition, when the batteries according to Examples 1 to 8 and Comparative Examples 1 to 3, whose capacities after 300 cycles were confirmed in Table 5, were disassembled to check the condition of the electrodeposited copper foil (which served as a cathode plate), it was confirmed that the electrodeposited copper foils according to Examples 1 to 8 had the same appearance as the original without any defects. On the other hand, it was confirmed that the electrodeposited copper foils according to Comparative Examples 1 to 3 were partially broken or peeled off.

[0069] Those skilled in the art will understand that the present invention can be embodied in other specific forms without changing the technical spirit or essential characteristics thereof. Therefore, the above-described embodiments should be understood to be illustrative in all respects and not limiting. The scope of the present invention is defined by the claims that follow, rather than the above detailed description, and all modifications and variations that fall within the meaning and scope of the claims and their equivalents should be construed as being within the scope of the present invention.

Claims

1. An electrolytic copper foil for a secondary battery, comprising TOC (total organic carbon), cobalt and iron, and formed by electrolytic plating using a plating solution, The TOC and the percentages of cobalt and iron measured after melting the electrolytic copper foil were: Formula 1 below: TOC / (cobalt + iron) = 1.3 to 1.5 and the TOC concentration in the plating solution is 450 to 1080 ppm. An electrolytic copper foil for a secondary battery, wherein the plating solution contains 1 mg / L to 50 mg / L of cobalt and 400 mg / L to 1100 mg / L of iron.

2. The electrolytic copper foil was subjected to a crosshead test for measuring the tensile strength at room temperature and at 110° C. (6 hours). The crosshead speed difference is expressed by the following formula 2: (1 mm / min crosshead speed tensile strength) / (50 mm / min crosshead speed tensile strength)≧0.9 in accordance with The electrolytic copper foil was subjected to a crosshead test for measuring the elongation rate at room temperature and at 110° C. (6 hours). The speed difference is expressed by the following formula 3: (1 mm / min crosshead speed elongation rate) / (50 mm / min crosshead speed elongation rate)≧0.8 The electrolytic copper foil for a secondary battery according to claim 1 .

3. The room temperature tensile strength of the electrolytic copper foil is 40 kgf / mm 2 ~51kgf / mm 2 The electrolytic copper foil for secondary batteries according to claim 1 ,

4. The electrolytic copper foil for a secondary battery according to claim 1, wherein the thickness of the electrolytic copper foil is 4 μm to 12 μm.

5. The electrolytic copper foil for a secondary battery according to claim 1, wherein the elongation ratio of the electrolytic copper foil is 2% to 18%.

Citation Information

Patent Citations

  • Electrolytic copper foil, electrolytic copper foil for lithium ion secondary battery, electrode for lithium ion secondary battery using the electrolytic copper foil, and lithium ion secondary battery using the electrode

    JP2012033475A

  • Copper alloy foil, manufacturing method of the same, electrode for lithium ion secondary battery with copper alloy foil as collector, and lithium ion secondary battery

    JP2013095954A

  • Electrolytic copper foil, electrode obtained using said electrolytic copper foil for lithium-ion secondary battery, and lithium-ion secondary battery obtained using said electrode

    WO2014119582A1

  • Electrolytic copper foil, and collector, negative electrode, and lithium battery comprising same

    WO2015142100A1